2016
DOI: 10.1208/s12248-016-9883-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G-protein Signaling (RGS)1 and RGS10 Proteins as Potential Drug Targets for Neuroinflammatory and Neurodegenerative Diseases

Abstract: Abstract. Regulator of G-protein signaling (RGS) proteins were originally identified as negative regulators of G-protein-coupled receptor (GPCR) signaling via their GTPase-accelerating protein (GAP) activity. All RGS proteins contain evolutionarily conserved RGS domain; however, they differ in their size and regulatory domains. RGS1 and RGS10 are smaller than other RGS proteins, and their functions involve various inflammatory responses including autoimmune responses in both the periphery and the central nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…Recent studies demonstrated also that SMC4 is associated with tumor progression and invasion and the expression of SMC4 is positively correlated with HIF-1a 30 . RGS1 protein is the most abundant RGS protein in the microglia and is a key gene of the immunomodulatory response to neuroinflammation as well as a key target of different immunological and neurodegenerative diseases such as multiple sclerosis, inflammatory bowel and Parkinson's disease 33,34 . Recent evidence suggests that RGS1 protein is involved in the hypoxia-dependent inflammatory response 35,36 , through activation of the AKT signalling pathway, which is switched-on after chronic moderate hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated also that SMC4 is associated with tumor progression and invasion and the expression of SMC4 is positively correlated with HIF-1a 30 . RGS1 protein is the most abundant RGS protein in the microglia and is a key gene of the immunomodulatory response to neuroinflammation as well as a key target of different immunological and neurodegenerative diseases such as multiple sclerosis, inflammatory bowel and Parkinson's disease 33,34 . Recent evidence suggests that RGS1 protein is involved in the hypoxia-dependent inflammatory response 35,36 , through activation of the AKT signalling pathway, which is switched-on after chronic moderate hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…RGS1 is expressed in lymphocytes, dendritic cells, monocytes (Bansal, Druey, & Xie, 2007), and microglia (Atwood, Lopez, Wager‐Miller, Mackie, & Straiker, 2011). It has been reported that B lymphocytes in germinal centers (GC) within follicles of lymphoid organs express especially high levels of RGS1 (Moratz et al, 2000), which codes for the regulator of G‐protein signaling 1, a protein located on the cytosolic side of the plasma membrane that acts as a negative regulator of G‐protein‐coupled receptors signaling (Lee & Bou Dagher, 2016). The fact that all chemokine receptors are coupled to heterotrimeric G‐proteins (Ansel & Cyster, 2001) promoted the investigation of the role of RGS1 in the response to chemokine stimulation and led to uncover that B cells in RGS1 −/− mice respond extremely to the chemokines CXCL12 (CXCR4 ligand) and CXCL13 (CXCR5 ligand; Moratz, Hayman, Gu, & Kehrl, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…With nearly every new function revealed, the role of a small molecule that would be useful as a drug or probe molecule for further investigation can be inferred. There are a number of recent publications on RGS proteins in cancer (17), inflammation (18), cardiovascular processes (19 -21), neuroinflammation (22), and even pregnancy (23, 24) that describe the diverse role RGS proteins play in these processes. In this review we will present examples that help reinforce the rationale behind the search for RGS inhibitors, in particular, those focused on neurological disorders and cancer.…”
Section: Why Target Rgs Proteins?mentioning
confidence: 99%
“…SNPs (rs2332700 and rs4899412) in RGS6 provide genetic evidence for the association of RGS6 with schizophrenia and Alzheimer's disease, respectively (56,57). Additional SNPs found in other RGS proteins suggest a genetic predisposition for certain central nervous system disease states (22,58), such as a SNP found in RGS1 (rs10492972) that is significantly associated with the diagnosis of multiple sclerosis (22,59).…”
Section: Rgs Proteins In Neurological Processesmentioning
confidence: 99%